THE PERSPECTIVE OF SPORT ACTIVITY IN DEVELOPING THE VALUE OF SPORTIVITY - Sridadi, Sridadi; Utami, Nur Sita; Broto, Danang Pujo; Saryono (Universitas Negeri Yogyakarta, 2025)
Perspektif aksiologi olahraga dalam pengembangan nilai sportivitas bertujuan menggali informasi dan melakukan analisis kritis guna menumbuhkembangkan nilai yang terkandung dalam olahraga khususnya nilai sportivitas. Nilai sportivitas menjadi bagian penting dalam olahraga, karena setiap insan olahraga harus menjunjung tinggi nilai-nilai yang menjadi bagian dari pengembangan karakter agar menjadi bangsa yang beradab dan berbudaya. Data yang dikumpulkan berupa data primer dan sekunder dari sumber-sumber kepustakaan. Analisis data menggunakan studi hermenautika untuk mendapatkan pemahaman hakekat nilai menggunakan kajian literasi dari sumber kepustakaan. Kepustakaan yang dikaji terkait pandangan nilai-nilai olahraga dari sudut pandang aksiologi. Hasil kajian memberikan ulasan bahwa dengan sudut pandang aksiologi, olahraga ternyata memiliki banyak sekali nilai yang dapat dipetik dan dikembangkan, salahsatunya adalah sportivitas. Agar nilai sportivitas itu menjadi perilaku yang melekat pada diri seseorang maka harus mulai ditanamkan sejak usia dini melalui pendidikan formal, informal dan nonformal.THE PERSPECTIVE OF SPORT ACTIVITY IN DEVELOPING THE VALUE OF SPORTIVITY AbstractsThe perspective of sports axiology in developing the value of sportsmanship aims to gather information and conduct critical analysis in order to develop the values contained in sports, especially the value of sportsmanship. The value of sportsmanship is an important part of sports, because every sports person must uphold the values that are part of character development in order to become a civilized and cultured nation. The data collected is in the form of primary and secondary data from library sources. Data analysis used hermenautic studies to get an understanding of the nature of values using literacy studies from literature sources. The literature studied relates to the viewpoint of sports values from an axiological point of view. The results of the study provide an overview that from an axiological point of view, sport has many values that can be learned and developed, one of which is sportsmanship. In order for the value of sportsmanship to become a behavior that is inherent in a person, it must be instilled from an early age through formal, informal and non-formal education.